Semisynthetic oleanane triterpenoids inhibit migration and invasion of human breast cancer cells through downregulated expression of the ITGB1/PTK2/PXN pathway. (25th April 2017) - Lisiak, Natalia; Paszel-Jaworska, Anna; Totoń, Ewa; Rubiś, Błażej; Pakuła, Martyna; Bednarczyk-Cwynar, Barbara; Zaprutko, Lucjusz; Rybczyńska, Maria
Abstract: This paper reports a study on the role of two synthetic derivatives of oleanolic acid (OA), HIMOXOL and Br-HIMOLID, in the regulation of cell migration and invasion and the underlying molecular mechanisms of breast cancer cells. The effect of the compounds on four breast cancer cell lines (MCF7, MDA-MB-231, MDA-MB-468, and T-47D) and also on noncancerous breast cells, MCF-12A, was reported. The compounds had no effect on the migration of MCF-12A cells. However, both the derivatives revealed a higher cytotoxicity than the maternal compound OA, and in sub-cytotoxic concentrations, they decreased the migration of MCF7, MDA-MB-231, and MDA-MB-468 breast cancer cells and also the invasion of MCF7 and MDA-MB-231 cells; although, the derivatives had no effect on the migration and invasion of T-47D cells. Both the derivatives of OA inhibited the cell migratory and invasive abilities of breast cancer cells by downregulating the expressions of ITGB1, PTK2, and PXN genes and by decreasing the phosphorylation status and the level of its respective proteins (integrin β1, FAK, and paxillin, respectively). This study is the first to report the antimigratory and anti-invasive activities of HIMOXOL and Br-HIMOLID in breast cancer cells. Highlights: HIMOXOL and Br-HIMOLID had no effect on the migration of MCF-12A cells. Both compounds decreased the migration and the invasion of breast cancer cells. The both derivatives downregulated the expression of ITGB1 / PTK2 / PXN pathway.